2011
DOI: 10.1128/jvi.05633-11
|View full text |Cite
|
Sign up to set email alerts
|

ISG56 and IFITM1 Proteins Inhibit Hepatitis C Virus Replication

Abstract: Hepatitis C virus (HCV) is a hepatotropic Flavivirus in theHepacivirus genus. The virus genome contains a linear, positive-strand RNA molecule of ϳ9,500 nucleotides. The HCV genome encodes a polyprotein precursor of about 3,000 amino acids, which is cleaved by both viral and host proteases into structural (core, E1, E2, and p7) and nonstructural (NS2, NS3, NS4A, NS4B, NS5A, and NS5B) proteins. A number of HCV genomes have been cloned, and sequence divergences indicate several genotypes and a series of subtypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(127 citation statements)
references
References 46 publications
9
113
1
Order By: Relevance
“…Compared with other viruses inhibited by IFITM proteins, the restriction of RSV was more profound than for human immunodeficiency virus, hepatitis C virus and influenza virus A at the same m.o.i. (Huang et al, 2011;Lu et al, 2011;Raychoudhuri et al, 2011). However, Rift Valley fever virus infection also displayed intensive inhibition by IFITM3 (Mudhasani et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other viruses inhibited by IFITM proteins, the restriction of RSV was more profound than for human immunodeficiency virus, hepatitis C virus and influenza virus A at the same m.o.i. (Huang et al, 2011;Lu et al, 2011;Raychoudhuri et al, 2011). However, Rift Valley fever virus infection also displayed intensive inhibition by IFITM3 (Mudhasani et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one family of ISGs, called IFN-inducible transmembrane (IFITM) proteins, and known to play diverse roles in cell signalling, adhesion, tumour genesis and immune regulation, was found to have the ability to restrict the cell entry and replication of a number of viruses. Most of the viruses restricted by the IFITM proteins are enveloped viruses, such as influenza A, dengue virus and West Nile virus (Brass et al, 2009;Weidner et al, 2010;Huang et al, 2011;Lu et al, 2011;Raychoudhuri et al, 2011;Mudhasani et al, 2013), but reovirus, which is a non-enveloped dsRNA virus, was also recently reported to be sensitive to IFITM3 repression (Anafu et al, 2013). IFITM3 has been reported to restrict cell infection of RSV and control disease pathogenesis in the Ifitm3 knockout mouse model (Everitt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The IFIT family, especially IFIT1 and IFIT3, restrict DNA and RNA virus replication, such as hepatitis B virus (HBV), human papillomavirus (HPV), hepatitis C virus (HCV), West Nile virus (WNV) and others [26,30]. Knock down of IFIT1 though RNA interference in human hepatocytes enhanced HCV replication during infection [31]. Eukaryotic translation initiation factor 4H (eIH4) is involved in regulation of translation initiation during protein synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…expression by various members of the IFN-family, as ISGs have been reported to play important roles in IFN-mediated antiviral activity (35,36).…”
Section: Discussionmentioning
confidence: 99%